2016
DOI: 10.1186/s12986-016-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary green-plant thylakoids decrease gastric emptying and gut transit, promote changes in the gut microbial flora, but does not cause steatorrhea

Abstract: Green-plant thylakoids increase satiety by affecting appetite hormones such as ghrelin, cholecystokinin (CCK) and glucagon-like peptide-1 (GLP-1). The objective of this study was to investigate if thylakoids also affect gastrointestinal (GI) passage and microbial composition. To analyse the effects on GI passage, 16 rats were gavage-fed a control or thylakoid-supplemented high-fat diet (HFD) 30 min before receiving Evans blue. Another 16 rats were fed a control HFD or thylakoid HFD for two weeks prior to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
0
26
0
3
Order By: Relevance
“…An increased release of satiety hormones suggests a delayed absorption of nutrients from the intestine during digestion through thylakoid membranes. In previous publications, we have found no evidence of increased faecal fat excretion by the addition of thylakoids despite body weight and fat mass loss, neither in man [9], nor in rat [7]. The thylakoid enriched high-fat diet used in mice was the same as previously used for rat, suggesting a species difference.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…An increased release of satiety hormones suggests a delayed absorption of nutrients from the intestine during digestion through thylakoid membranes. In previous publications, we have found no evidence of increased faecal fat excretion by the addition of thylakoids despite body weight and fat mass loss, neither in man [9], nor in rat [7]. The thylakoid enriched high-fat diet used in mice was the same as previously used for rat, suggesting a species difference.…”
Section: Discussionmentioning
confidence: 77%
“…There might also be a reduced fat absorption or an increased fatty acid oxidation. We however found no sign of steatorrhea in spite of a body weight loss, neither in rodent studies [7] nor in human studies [8, 9]. We also observed an increased expression of fat oxidative enzymes in the gut and an increased fat oxidation in rat fed high-fat diet with thylakoid supplementation [10], suggesting other mechanisms to explain the fat mass reduction.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Due to the lack of studies regarding the effects of spinach-derived thylakoids on lipid metabolism, the mechanism by which thylakoid-rich spinach extract might affect lipid pro le are still unknown. The existing evidence shows that the prebiotic effect of spinach thylakoids, and hence, modulation of gut microbiota may be involved in the lipid-lowering properties of the thylakoid-rich spinach extract [38,57]. In this regard, it is demonstrated that spinach thylakoid consumption induces fatty acid oxidation and inhibits de novo synthesis of lipids through increasing the generation of shortchain fatty acids (SCFAs).…”
Section: Discussionmentioning
confidence: 99%
“…39) Moreover, Stenblom et al have reported that a delay in gastric emptying mediated by food intake. 40) Therefore, this phenomenon may be ascribed to the fact that gastric emptying was delayed by thylakoid-rich spinach extract. 41) Conversely, we observed that the T max of GF and IM was not affected by thylakoid-rich spinach extract; this is likely because dissolution is a rate-limiting step for gastrointestinal absorption of GF and IM, which are poorly water-soluble.…”
Section: Discussionmentioning
confidence: 99%